MAKSUD TUTURAN SUMIMASEN PADA ANIME JEPANG - Sindy Octa Clarita; Arza Aibonotika; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research is to explain meanings of sumimasen in Japanese animation based on context. This research was conducted using a qualitative approach and the type of the research is a descriptive research. The method that was used by the researcher in collecting the data in this research is the note-taking method. First, the researcher watched anime Mushoku Tensei, Saint’s Magic Power is Omnipotent, Hyouka, Gakuen Babysitter, Slime 300, Mob Psycho and Koi wa Ameagari. Researcher then searched, listened and recorded the data found. The results that were obtained are 15 sumimasen which resulted with 5 classifications.Key Words: Sumimasen, Anime, Japanese language education.